Design and analysis of a dual-rope crawler rope-climbing robot - J. Wang; J. Wang; L. Yin; R. Du; L. Huang; J. Huang (Mechanical Sciences, 2024)
A rope-climbing robot (RCR) can reciprocate on a rope. To address the problems of poor load capacity and adaptability of the existing RCR, this study designs a dual-rope crawler type RCR, which can be used as a new type of transportation equipment in hilly, mountainous, and plateau areas. The crawler rope-climbing mechanism is a combination of a chain drive and the rope-climbing foot. Innovatively applying the parabolic theory of overhead rope to kinematically analyze the rope-climbing robot system, the robot motion trajectory model and the tilt angle equation are established. To establish the safe working interval of the rope-climbing robot, the influence of machine load and rope span on robot tilt angle is compared. Furthermore, research on the dynamic characteristics of the rope-climbing robot is carried out, establishing a time-varying system model of the dynamic tension of the rope in the rope-climbing robot system and analyzing the effects of speed and load on the dynamic tension of the rope and system stability. Finally, the prototype test results show that the RCR operates stably and has good load capacity and barrier-crossing capability.